2021
DOI: 10.1177/15357597211014195
|View full text |Cite
|
Sign up to set email alerts
|

COVID-19 Incidence and Death Rate in Epilepsy: Too Early to Tell?

Abstract: [Box: see text]

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1

Citation Types

0
4
0

Year Published

2022
2022
2023
2023

Publication Types

Select...
4

Relationship

1
3

Authors

Journals

citations
Cited by 4 publications
(4 citation statements)
references
References 9 publications
0
4
0
Order By: Relevance
“…There was evidence early on that severe acute respiratory syndrome coronavirus-2 (SARS-CoV-2) can infect brain tissue. 1 Early studies on whether SARS-CoV-2 infection could cause seizures and resultant epilepsy and whether COVID-19 and its sequelae were more prevalent or severe in persons with preexisting epilepsy were difficult to interpret because SARS-CoV-2 antigen tests had not yet been developed or widely deployed. 1 -3 In 2020 and 2021, it was observed that COVID-19 patients hospitalized with severe pulmonary signs sometimes had encephalopathy, but acute seizures and status epilepticus appeared to be relatively uncommon.…”
Section: Commentarymentioning
confidence: 99%
See 1 more Smart Citation
“…There was evidence early on that severe acute respiratory syndrome coronavirus-2 (SARS-CoV-2) can infect brain tissue. 1 Early studies on whether SARS-CoV-2 infection could cause seizures and resultant epilepsy and whether COVID-19 and its sequelae were more prevalent or severe in persons with preexisting epilepsy were difficult to interpret because SARS-CoV-2 antigen tests had not yet been developed or widely deployed. 1 -3 In 2020 and 2021, it was observed that COVID-19 patients hospitalized with severe pulmonary signs sometimes had encephalopathy, but acute seizures and status epilepticus appeared to be relatively uncommon.…”
Section: Commentarymentioning
confidence: 99%
“…1 Early studies on whether SARS-CoV-2 infection could cause seizures and resultant epilepsy and whether COVID-19 and its sequelae were more prevalent or severe in persons with preexisting epilepsy were difficult to interpret because SARS-CoV-2 antigen tests had not yet been developed or widely deployed. [1][2][3] In 2020 and 2021, it was observed that COVID-19 patients hospitalized with severe pulmonary signs sometimes had encephalopathy, but acute seizures and status epilepticus appeared to be relatively uncommon. [4][5][6] Taquet et al questioned whether patients with COVID-19 were more likely than controls to develop seizures or epilepsy.…”
Section: Commentarymentioning
confidence: 99%
“…Although active epilepsy itself has not been associated with worse COVID-19 outcomes to date, several studies have suggested those with various neurologic conditions, disabilities, and mental health conditions in which epilepsy may co-occur (e.g., cerebral palsy, dementia, Down Syndrome) may be at higher risk for such outcomes [1] , [2] , [3] , [4] . Growing research has examined the effects of COVID-19 infection among people with epilepsy, safety and tolerability of the COVID-19 vaccines, and COVID-19 vaccination status among people with epilepsy [5] , [6] , [7] , [8] , [9] , [10] . A review examining COVID-19 vaccination coverage and willingness to be vaccinated against COVID-19 based on international samples of patients with epilepsy (up to April 30, 2022) reported suboptimal levels of COVID-19 vaccination coverage and intent to vaccinate [11] .…”
Section: Introductionmentioning
confidence: 99%
“…Therefore, failure to exclude patients infected with these viruses might have influenced the findings of the study. 2,3 Fourth, a study conducted in the United States pointed out disparities in the incidence of COVID-19, demonstrating that Hispanics and Blacks have an increased likelihood of getting this disease. 4 The results of this research emphasize the significant role of both race and ethnicity as confounders in studies involving COVID-19 patients.…”
mentioning
confidence: 99%